Nano-enabled natriuretic peptide therapy in post-myocardial infarction heart failure: from functional NP deficiency to dual-axis (cGMP-dependent and -independent) cardioprotection - Giulia Cevoli; Ivan Isaia; Reza Parvan; Horng H. Chen; Lorenzo Malatino; John C. Burnett; Alessandro Cataliotti (Internal and Emergency Medicine, 2026)
Abstract Myocardial infarction (MI) remains a major driver of incident heart failure (HF) despite timely reperfusion and guideline-directed medical therapy. Current treatments, largely centered on neurohormonal blockades, attenuate maladaptive pathways but do not restore endogenous cardioprotective systems. Among these, the natriuretic peptide (NP) network plays a central role in counteracting fibrosis, hypertrophy, sodium retention, and microvascular dysfunction. In advanced HF, impaired prohormone processing, corin dysfunction, and abnormal glycosylation lead to the predominance of biologically less-active NP forms despite elevated circulating levels, resulting in “functional NP deficiency” and insufficient NP–cGMP signaling. From a mechanistic perspective, NP biology can be organized into two complementary axes. The cGMP-dependent axis comprises ANP and BNP signaling via NPR-A and CNP via NPR-B, mediating natriuretic, vasodilatory, and antifibrotic effects. The cGMP-independent axis includes NPR C-mediated signaling and the actions of the ANP mid-sequence fragment proANP31-67, which exerts antifibrotic and cardioprotective effects through a cyclooxygenase−2/prostaglandin E₂/EP4 pathway with minimal systemic hypotension. Nanomedicine offers a strategy to restore these complementary pathways with improved spatiotemporal precision. Lipid and polymeric nanoparticles, biomimetic carriers, and extracellular vesicles can protect NP-derived cargo, prolong bioavailability, and enhance functional cardiac targeting while limiting off-target exposure, although current evidence is largely preclinical. In this review, we examine NP biology in post-ischemic remodeling, the concept of functional NP deficiency, and emerging nano-enabled delivery approaches as potential add-on interventions to contemporary HF therapy. We propose dual-axis “nano-hormonal” strategies integrating cGMP-dependent and cGMP-independent signaling as a testable paradigm for targeted modulation of post-MI remodeling.